MATHEMATICAL MODELING OF THE WIND FLOW AND THE TRANSFER OF POLLUTANTS IN ORDER TO PREDICT THE ENVIRONMENTAL SITUATION IN RESIDENTIAL AREAS - Nygmetova, A.; Issakhov, A. A. (Ķazaķstan-britan tehnikalyķ universitetìnìņ habaršysy, 2024)
This study aims to analyze the turbulent dispersion of pollutants in the city of Almaty, Kazakhstan, caused by vehicle emissions. The influence of the environment and building on the dispersion of pollutant concentration, in this case ethylene, was studied. A three-dimensional model was built to accurately describe an existing street in the city. Turbulent air flow and concentration was investigated using a mathematical model of convection in a cavity and was solved using the SST k-omega method. SIMPLE algorithm was applied to solve the velocity-concentration relationship. When comparing between the obtained results and known test data, the similarity of the identified results showed the correctness of the methods and algorithms used. In summary, the results of pollutant spreading were analyzed in the presence of a barrier of different heights: 1m, 2m and 3m. The findings indicate that the presence of barrier has a positive effect on the retention of pollutants. Also the height of these barriers plays an important role, so the planning and construction should be grounded on the outcomes of modeling and peculiarities of the given territory. This is proved by the marked differences in the amount of concentration at one and the same moment of time for all cases.